Theory and Practice of Digital Libraries Second International Conference, TPDL 2012, Paphos, Cyprus, September 23-27, 2012. Proceedings - Zaphiris, Panayiotis; Buchanan, George; Rasmussen, Edie.; Loizides, Fernando; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the refereed proceedings of the Second International Conference on Theory and Practice of Digital Libraries, TPDL 2012 - the successor of the ECDL (European Conference on Research and Advanced Technology for Digital Libraries) - held in Paphos, Cyprus, in September 2012. The 23 full papers, 19 short papers, 15 posters and 8 demonstrations presented in this volume were carefully reviewed and selected from 139 submissions. The papers are organized in topical sections on user behavior, mobiles and place, heritage and sustainability, preservation, linked data, analysing and enriching documents, content and metadata quality, folksonomy and ontology, information retrieval, organising collections, as well as extracting and indexing.
User Behaviour -- Heritage and Sustainability -- Preservation -- Linked Data -- Analysing and Enriching Documents -- Folksonomy and Ontology -- Information Retrieval -- Organising Collections -- Extracting and Indexing.
Keywords: Computer science; Database management; Data mining; Information storage and retrieval systems; Multimedia systems; Text processing (Computer science; Computer Science; Information Systems Applications (incl. Internet).; Database Management; Information Storage and Retrieval; Data Mining and Knowledge Discovery; Multimedia Information Systems; Document Preparation and Text Processing